Faktor yang Berkaitan dengan Tahapan Adopsi Petani terhadap Teknologi Mesin Rice Transplanter (Kasus pada Enam Subak di Kabupaten Tabanan) - FUJIARTA, PUTU ICHIRO; SARJANA, I DEWA GEDE RAKA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Factors Related to the Stages of Farmer Adoption of Rice Transplanter Machine Technology (A Case in Six Subaks in Tabanan Regency) Rice transplanter is a modern machine for planting rice seeds. The provision of the machine is to support the government program. The purpose of this study was to determine the extent of adoption and factors related to the adoption of rice transplanter machine. The research locations were in six subaks in Tabanan Regency using 89 respondents. The method used was qualitative descriptive analysis and scoring scale measurement. Based on the research result of adoption stage of rice transplanter machine has reached the implementation stage to be tested. Factors related to technology adoption, namely the nature of innovation that is known to be true as 88.76% of respondents. Farmers' perceptions of the usefulness and benefits of technology are quite good (score 758 including class > 695-909) and perceptions of ease of technology are quite difficult (score 726 including class > 695-909). The target attitude wants to implement and the need for technology is very low (a score of 155 and a score of 143 is included in classes 89-160). The target behavior in accepting innovation was low, only 12.36% of respondents received. For the use of innovation, only 12.36% of respondents used innovation to try.